Gender wage differences in the Philippines labour market. - Choong, Elizabeth Jia Yun. (2010)
This study aims to determine the factors contributing to the gender wage gap in the Philippines, using 2006 Labour Force Survey (LFS) data, by decomposing the gender gap along the entire conditional distribution of wages. We use the newly available STATA module rqdeco, which generalizes the Oaxaca-Blinder decomposition to any quantile of the earnings distribution.